Deixa que digam, pensem, falem: representações juvenis sobre a violência racial no território escolar - Pereira da Silva, Ângela Maria; Salazar Guizzo, Bianca (ILUMINURAS, 2021)
Deixa que digam, pensem, falem: representações juvenis sobre a violência racial no território escolar